Nelson’s Syndrome: Questions and Answers (Clinical Case) - Z.P. Nizhinska-Astapenko; M.V. Vlasenko; N.I. Hurina (Mìžnarodnij Endokrinologìčnij Žurnal, 2016)
This clinical case reflects the variability in the course of chronic adrenal insufficiency after bilateral adrenalectomy for Itsenko — Cushing disease, the development and growth of pituitary adenoma, which can lead to hemorrhagic stroke in the most recurrent pituitary tumor. The objective of pathogenetic treatment is to reduce the secretion of adrenocorticotropic hormone secretion, to restore normal secretion of tropic pituitary hormones, as well as the prevention of further growth of pituitary tumor and adequate compensation of adrenal insufficiency. The case shows labile course of postoperative adrenal insufficiency and, consequently, different approaches to the diagnosis and the need for substitution therapy at different stages of the disease.